Social cognitive determinants of exercise intentions and behaviour in patients with coronary artery disease - Tulloch, Heather (University of Ottawa (Canada), 2007)
Coronary artery disease (CAD) remains to be the leading cause of death in developed countries. Exercise is a core factor in the secondary prevention of CAD, yet most patients diagnosed with CAD fail to meet exercise guidelines. Thus, new exercise interventions are required. Before interventions are developed, increased theory-based knowledge regarding modifiable exercise determinants is needed. The overall purpose of this dissertation was to examine the determinants of exercise intentions and behaviour over time in patients with CAD. More specifically, we tested a model based on social cognitive theory (SCT) in the prediction of exercise outcomes in two studies. First, in preparation for a larger cohort study, we conducted a cross-sectional pilot study that investigated which SCT variables appeared to be most strongly associated with the exercise intentions of 214 patients with CAD. Using structural equation modeling, results demonstrated that the model was a good representation of the relationships within the data. The SCT variables accounted for a large amount (54%) of the variance in exercise intentions in patients with heart disease. Intentions were influenced mainly by participants' self-efficacy and moderately by outcome expectations. Previous exercise, social support, and supportive physical environments also contributed to patients' intentions indirectly through self-efficacy and outcome expectations. Building from these results, the second study used a prospective longitudinal design to test a more comprehensive SCT model in the prediction of 770 cardiac patients' exercise behaviour at two time points. More precisely, we examined the relationships between previous exercise, physiological feedback, positive and negative social environments, supportive physical environments, self-efficacy, outcome expectations, exercise intentions and exercise behaviour 6 months (time 1) and 12 months (time 2) after a CAD-hospitalization. Again, the model was a good fit to the data, and accounted for 22% and 34% of the variance in the participants' exercise behaviour at 6 and 12 months, respectively. Results indicated that previous exercise exerted the largest total effect on exercise behaviour at both time points, followed by self-efficacy. At time 1, supportive physical environments and exercise intentions also had significant direct links to exercise behaviour. At 12 months, participants' self-efficacy and outcome expectations predicted exercise behaviour directly. These studies provided support for the utility of SCT in the prediction of exercise outcomes in patients with CAD. Our findings also suggest ways to increase exercise behaviour in this population.
Keywords: Health Sciences, Rehabilitation and Therapy.; Psychology, Behavioral.; Psychology, Social.